Scolopocryptops longipes sp. nov., a troglobitic scolopocryptopine centipede (Chilopoda: Scolopendromorpha: Scolopocryptopidae) from China - Xiao, Shuqing; Chen, Huiming; Di, Zhiyong (Zootaxa, 2021)
We describe Scolopocryptops longipes sp. nov., a new troglobitic scolopocryptopine centipede species from a karstic area in southern China. The species was found in Shuiba Cave of Libo County, Guizhou Province. The cephalic plate wider than long, with complete margination along the lateral margin of cephalic plate; TT6–19 with complete paramedian sutures; tibia, tarsus 1 and tarsus 2 of leg 22 each with one spur; prefemur and femur of ultimate legs glabrous, tibia and tarsi with dense bristles. S. longipes is the second troglobitic scolopocryptopine in China and the fourth in the world described thus far.